[P04] A Single Centre Early Experience of Directional Atherectomy in Managing Lower Limb Ischaemia. (November 2022) - El-Sayed, Tamer; Altahir, Albagir; Thomas, Matthew; McCaslin, James; Nesbitt, Craig
Abstract : Objective: Directional atherectomy has increasingly become an effective and safe endovascular technique in treating patient with claudication and critical limb threatening ischaemia (CLTI). This study reports a single centre early experience of using directional atherectomy. Methods: This was a retrospective study of prospectively collected data of patients who underwent directional atherectomy for short distance claudication or CLTI in the Northern Vascular Centre, Freeman hospital, Newcastle. Three month primary patency, secondary patency, limb salvage/amputation, technical success, adverse events, and median lesion length were analysed. Results: Twenty five patients (median age 69 years, range 35 – 88) underwent directional atherectomy between 2019 and 2021 for debilitating short distance claudication and critical limb threatening ischaemia. Patients were either unfit for major open revascularisation bypass or had hostile groin. The HawkOne directional atherectomy system (Medtronic, USA) was used to treat 18 femoral-popliteal arteries, three external iliac arteries, and four external iliac and common femoral arteries with a median lesion length of 96.3 mm (70 – 109). Success rates were 96% technical success with primary patency of 88%, with 100% success in resolving rest pain in CLTI and improving claudication distance to more than 200 m. Four patients required re-intervention with secondary patency of 96%. Three adverse events were observed (two distal embolisation and one intimal dissection). A 96% limb salvage rate with 4% mortality was recorded for intra-operative bleeding. Conclusion: Directional atherectomy showed promising technical and clinical short term outcomes in selective cases. Multicentre randomised controlled trials are required for better understanding of the long term outcomes in managing patients with peripheral arterial disease.